THE EFFICACY OF GREEN TEA (Camellia sinensis) LEAVES EXTRACT AS CORROSION INHIBITOR FOR ORTHODONTICS STAINLESS-STEEL WIRE (Research report) - Neny Roeswahjuni; Delvi Fitriani; Annisa Dwi Wardanianti (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Stainless-steel orthodontic wire is one of appliance component frequently used in orthodontics treatment and persisted in oral cavity for an extended period, thus may generate corrosion via ion release. An attempt to reduce corrosion rate is by using organic inhibitor which contains antioxidant. This substance can be simply found in green tea leaves. Objective: To discover the efficacy of green tea leaves as a corrosion inhibitor for stainless-steel orthodontic wire. Methods: It is an experimental laboratory research with post-test only control group design. As many as 24 samples were divided into 4 groups which immersed in artificial saliva: one group without any treatment and 3 groups given green tea leaves extract, each in 6.25%, 12.5% and 25% concentration. Corrosion rate was measured using potentiodynamic methods (Tafel). Data was analyzed using one way ANOVA test followed by post-hoc tukey HSD test. Result: There was significant difference in corrosion inhibitory efficacy among treatment groups (p<0.05). The highest corrosion rate value was found in no-treatment group (average value 0.195). The highest corrosion rate reduction was found in treatment group number four supplemented with 25% concentration of green tea leaves extract as inhibitory substance (p=0.0325). Conclusion: Green tea leaves extract is proven to be effective as corrosion inhibitor for stainless-steel orthodontic wire.